Psychological trauma and childhood - Levett, Ann (PINS-Psychology in Society, 2025)
Experiences of sudden unexpected physical injuries and danger to life have psychological effects in the sense that strategies are mobilized to ensure personal survival and safety. Ideas about psychological trauma in childhood, however, are bound up with differently conceived issues. Firstly there are preoccupations with certain events or situations and these are emphasised over others. Secondly, there are dominant ideas concerning evidence of trauma; these are widely held. Particular models of childhood, i.e. discourses of childhood, are always involved in talk about psychological trauma in children. This paper examines current notions about the causes of variations in children's behaviours (or problems in children) and discloses for scrutiny the ways in which four major discourses of childhood (passive, innocent, organismic and cognitive/rational) interact with these causative models to construct and perpetuate particular views of psychological trauma.